Application of Heberprot-P® in a patient with neuroinfectious diabetic foot - Lyudmila Verdaguer Pérez; Lisbet Estrada Ladoy; Jacqueline Bertrán Bahades (Centro Provincial de Información de Ciencias Médicas, 2017)
The case report of a 51 years patient with type 2 diabetes mellitus for around 26 years is described, to whom neuroinfectious diabetic foot was diagnosed.  Initially, he  was admitted to the  Angiology Service of "Saturnino  Lora Torres" Teaching Clinical Surgical Provincial Hospital  in Santiago de Cuba, where Heberprot-P® was indicated as part of the treatment, first 3 bulbs of 75 mg each and then 8 bulbs of 25 mg; the latter were applied in an ambulatory way in the polyclinic of his health area.  After 11 weeks of beginning the therapy the total scaring of the lesion was achieved.